Revealing Author’s World View About Cowboy and The Frontier Life in Seth MacFarlane’s A Million Ways to Die in the West - Ana Widiyanti; Niken Kencono Ungu (Metaphor, 2019)
This library research paper aims to reveal the author’s world view about American cowboy/cowgirl and the American frontier life. The subject of the study is a novel entitled A Million Ways to Die in the West written by Seth MacFarlane. This research will apply genetic structuralism theory. Furthermore, to understand the context deeper, some supporting data concerning the history of cowboy/cowgirl and the frontier life are also applied. With MacFarlane well known specific writing style, his novel is different and unique, whereby he blends irony as well as humor in it. His world view about cowboy/cowgirl and the frontier life is quite negative although he ends the story with a happy ending. He considers most of the cowboys are brutal, mean, and extravagant. While he considers living in the frontier is tough because the frontier is a kind of uncivilized place to live. His negative view is mostly presented through the representation of some characters’ characterization, especially from the male and female protagonist characters.